Genome-wide mutational biases fuel transcriptional diversity in the Mycobacterium tuberculosis complex - Álvaro Chiner-Oms (Nature Portfolio, 2019)
A variety of biological differences exist between strains and phylogenetic lineages in the Mycobacterium tuberculosis complex (MTBC). Here, the authors perform RNAseq and methylome analysis of the main clades of the MTBC and show variation in transcriptional profiles is mainly due to mutations in transcriptional start sites.